(untitled) (ҚазҰУ хабаршысы. Экология сериясы, 2021)
The article presents the results of a study of the spatial structure of vegetation SNNP (State National Nature Park) «Sharyn» on the basis of the inventory and assessment of vegetation in SNNP «Sharyn» in Almaty region. The spatial distribution of the SNNP «Sharyn» vegetation cover was based on the landscape structure of the territory and ecological and physiognomic types of vegetation. The assessment of Botanical diversity of vegetation included an assessment of floral and phytocenotic diversity of vegetation. The floral diversity of the SNNP «Sharyn» vegetation cover consists of 915 species of vascular plants from 406 genera and 84 families, which indicates a significant species richness of the flora. According to the Botanical and geographical division, the vegetation of the territory under consideration belongs to the Sahara-Gobi region, the Iran-Turan subdistrict, the Dzungarian province and belongs to the intermountain-basin deserts. The taxonomic analysis of the flora of the SNNP «Sharyn» showed that the 10 leading families include 578 species, or 63.12% of the total number of species. The spatial heterogeneity of the vegetation cover of the SNNP «Sharyn» includes the vegetation of low-mountains, low-hills, foothill plains, ariddenudation plateaus, deluvial-proluvial plains, ancient alluvial plains, canyons and dry channels, valleys of the Temirlik and Sharyn rivers, anthropogenically disturbed agricultural lands. The result of the assessment of the spatial distribution of vegetation cover was the creation of a vegetation map at a scale of 1: 300000. The created map contains 39 allotments. Key words: Sharyn, floristic and phytocenotic diversity, inventory monitoring.